Determination of Relative Sedimentation Velocity using Benthic Foraminifera in Pasaman Barat Sasak Beach Waters West Sumatra Province - Firmansyah, Firmansyah; Rifardi, Rifardi; Tanjung, Afrizal (Jurnal Perikanan dan Kelautan, 2019)
This research was conducted in May - August 2018 in the waters of Sasak Beach Pasaman Barat, West Sumatra Province. The purpose of this research was to determine the relative sedimentation velocity, the type of benthic foraminifera, and the distribution pattern of benthic foraminifera in the waters of Sasak Beach Pasaman Barat, West Sumatra. The method used in this research is purposive sampling method which is divided into 3 stations. The highest relative sedimentation velocity is found at Station I with a value of 28.0%, the relative sedimentation velocity is highest at station II with a value of 35.0%, and at station III 20.0%. The most commonly found foraminifera species are Ammonia beccarii, Quinqueloculina disparilis and Quinqueloculina laviegata. Benthic foraminifera from 3 observation stations can be divided into 6 groups. Group I was characterized by Ammonia beccarii (Line Form B), Ammonia beccarii (Line Form C), Textularia aglutinans and Trochammina inflate. Group II is characterized by Ammonia beccarii (Line Form A, B and C), Nonionoides gratelouupi, Quinqueloculina laviegata, and Spiroloculina laviegata. Group III is characterized by Ammonia beccarii (Line Form A, B and C), Spiroloculina laviegata, and Triloculina oblonga. Group IV is characterized by Ammonia beccarii (Line Form A, B and C), Nonionoides gratelouupi, Quinqueloculina disparilis, and Miliolina subrotunda. Group V is characterized by Ammonia beccarii (Line Form A, B and C), Quinqueloculina laevigata and Spiroloculina laevigata. Group VI is characterized by Ammonia beccarii (Line Form A, B and C), and Sigmoilinita distort. The distribution pattern of benthic foraminifera tends to clumped